Changing characteristics of maize drought in different climate zones of China based on the continuous days without available precipitation - Yue Qi; Heling Wang; Yurui Tang; Yang Yang; Hong Zhao; Funian Zhao; Kai Zhang; Fei Chen; Xingxing Wei; Xiaofeng Yang (Theoretical and Applied Climatology, 2026)

Subchronic exposure of tire wear particles leachate induces oxidative stress and DNA damage in zebrafish (Danio rerio) brain - Bo Cheng; Yurui Hou; Yuqing Hou; Lanjun Wang; Yibo Gao; Yuhan Ye; Tao Tang; Baihui Shi; Junpu Wang; Lusheng Zhu; Jun Wang; Young Mo Kim; et al. (Journal of Environmental Management, 2026)

Gobi-sourced dust and dust–climate feedbacks in the March 2023 East Asian storm - Shuna Liang; Bin Wang; Yurui Zhang; Junhua Yang; Ove W. Haugvaldstad; Hui Tang (Atmospheric Research, 2026)

Fluid evolution in the Naxi Fe polymetallic deposit, Eastern Kunlun, China: Insights from in-situ trace element and sulfur isotope compositions of pyrite and pyrrhotite - Rongqiang Guo; Shijiong Han; Chenggang Cao; Kaizhang Shi; Yurui Yuan; Mingyu Tang; Jinxin Yuan; Yongkun Fang; Yushan Jia (Journal of Asian Earth Sciences, 2026)

Impacts of Qinling Mountains Elevation on Precipitation in Central China: A WRF Modelling Analysis - Bin Wang; Yiru Yang; Peter Clift; Wenting Gao; Li Xing; Yurui Zhang; Chris Brierley; Ting Sun; Hui Tang; Wei Shang; Ying Cheng; Shuangshuang Li; et al. (International Journal of Climatology, 2025)
The tectonically driven uplift of the Qinling Mountains during the Cenozoic may have resulted in significant climatic and environmental effects, but this remains poorly understood. This study investigates the influence of the Qinling Mountains' uplift on summer precipitation patterns in central China using the Weather Research and Forecasting (WRF) model to design topographic sensitivity experiments. The results show that the uplift of the Qinling Mountains leads to the intensification of the spatial distribution of precipitation in China, with increased precipitation in the south and decreased precipitation in the north. The uplift of the Qinling Mountains from an average elevation of 400 m to their current elevation results in a 13% (64.3 mm) decrease in precipitation north of the Qinling Mountains, a 39% (134.4 mm) increase in the Qinling Mountains, and a 1.5% (8.1 mm) increase to the south. In particular, precipitation in the Loess Plateau decreased by 62.7 mm (18%). As the Qinling Mountains uplift, the physical barrier effect is enhanced, leading to a reduction in water vapour over the Qinling Mountains. However, the forced uplift of air masses results in enhanced vertical motion, which in turn increases summer precipitation over the Qinling Mountains. In contrast, although water vapour accumulation occurs to the north of the Qinling Mountains, the absence of topographic forcing leads to decreased precipitation. When the Qinling Mountains uplifted to an average elevation of 1600 m, they began to exert a more pronounced blocking effect on wind and water vapour transport. This elevation effectively transformed the Qinling Mountains into a natural barrier, further separating the climatic regimes of the north and south of China. These findings indicate that the changes in elevation during the uplift of the Qinling Mountains have had a marked impact on the spatial distribution of precipitation in the central China.

Climate and land use regulate vegetation–runoff interaction pathways in the three-river source region - Guiyuan Zhang; Darrell Tang; Song Li; Yurui Fan; Alim Pulatov; Aili Sun; Xingyun Qi; Licheng Wang; Yi Li (Journal of Environmental Management, 2025)

A 5-year field study to assess interannual variability and determinants of cotton fiber quality in intercropping systems - Haoyue Qin; Yurui Tang; Xin Li; Yurong Qiu; Jian Wang; Yingchun Han; Guoping Wang; Shiwu Xiong; Minghua Xin; Wenli Du; Lu Feng; Yongjiang Zhang; et al. (European Journal of Agronomy, 2025)

Research on intercropping from 1995 to 2021: a worldwide bibliographic review - Yurui Tang; Yurong Qiu; Yabing Li; Huasen Xu; Xiao-Fei Li (Plant and Soil, 2025)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

An algal-bacterial symbiotic system of carbon fixation using formate as a carbon source - Yurui Zheng; Jeffrey J. Czajka; Carly Daiek; Zhichang Yang; Liangliang Sun; Yinjie J. Tang; Yan Liu; Wei Liao (Algal Research, 2023)

Characterization of the cellulolytic bacteria communities along the gastrointestinal tract of Chinese Mongolian sheep by using PCR-DGGE and real-time PCR analysis - Yan Zeng; Dong Zeng; Yan Zhang; Xueqin Ni; Yurui Tang; Hui Zhu; Hesong Wang; Zhongqiong Yin; Kangcheng Pan; Bo Jing (World Journal of Microbiology and Biotechnology, 2015)

Viable Intestinal Passage of a Canine Jejunal Commensal Strain Lactobacillus acidophilus LAB20 in Dogs - Yurui Tang; Per E. J. Saris (Current Microbiology, 2014)